Botswana as a role model for country success - James A. Robinson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
I argue that the economic success of Botswana can be explained by the historical development of its institutions which is related to the trajectory of the Tswana states over the past 200 years. These institutions created a much more stable and accountable government than elsewhere in Africa after independence with the desire and incentive to adopt good economic policies. There are two main lessons from this experience. The first is how successful an African economy can become using simple orthodox well-understood policies. The second is that successful development in Africa will be helped by a focus on the development of state institutions. Though Botswana inherited different institutions from elsewhere, it also built on these, in particular trying to create a national identity and to continually modernize and adapt institutions. There are many lessons for other African countries from these policy choices.
Keywords: O10; H1; 330; governance; patrimonialism; state formation; Entwicklung; Governance-Ansatz; Regierung; Botsuana